Consumer capitalism : politics, product markets, and firm strategy in France and Germany - Trumbull, Gunnar (Cornell studies in political economy., 2006)
"Gunnar Trumbull investigates the origins of national systems of consumer protection in France and Germany, where, in the early 1970s, consumer groups and producers organized to advance their own ideas about the identity and interests of the affluent consumer. Through a comparison of eight areas of policy, Trumbull shows that different conceptions of the consumer interest emerged in the two countries. The result was the development of distinctive national consumption regimes, which have in turn influenced the market strategies of domestic producers."